Banking liquidity risk management in Ukraine based on the application of digital and information technologies - Dziamulych, Mykola; Krupka, Ihor; Andruschak, Yevheniia; Petyk, Marta; Paslavska, Roksolana; Grudzevych, Yulia; Martyniuk, Rostyslav (Magnanimitas AG, 2022)
The article discusses the peculiarities of liquidity risk management in modern conditions. The advantages of the transition to the use of liquidity standards determined by the provisions of Basel III have been determined. The higher efficiency of the LCR and NSFR standards, compared to the liquidity ratios previously used by the National Bank of Ukraine, has been proven. The peculiarities of the dynamics of liquidity standards in the banking system of Ukraine in general have been determined. The specifics of the impact of modern information and digital technologies on bank liquidity risk management are considered. The process of digital transformation of the liquidity management system based on the application of digital software solutions for liquidity risk analysis and forecasting is considered.
Keywords: Digital technologies; LCR; Liquidity; Liquidity standards; NSFR